Impact of Diarrhea on the Clinical Presentation and Outcome of Severe Pneumonia in Bangladeshi Children. Issue 10 (October 2016) - Chisti, Mohammod Jobayer; Duke, Trevor; Salam, Mohammed Abdus; Shahunja, K. M.; Shahid, Abu S. M. S. B.; Bardhan, Pradip Kumar; Faruque, Abu S. G.; Ahmed, Tahmeed
Abstract : We compared clinical presentation and outcome of 225 children with severe pneumonia between those with and those without diarrhea. Having diarrhea was associated with metabolic acidosis ( P < 0.001) and hypocalcemia ( P = 0.002) on presentation, and with a fatal outcome: 20/113 (20%) died with diarrhea versus 3/112 (3%) without diarrhea. Diarrhea is an important comorbidity in Bangladeshi children with severe pneumonia requiring attention for improved case management. Abstract : Supplemental Digital Content is available in the text.